Cronkhite- Canada Syndrome - Narendra; Shenoy S D; Bejoy P; Srinivas C R (Wolters Kluwer Medknow Publications, 1997)
A case of Cronkhite- Canada syndrome in a 59 year old male is reported. The patient presented with generalized hyper pigmentation, alopecia, loss of finger and toenails, diarrhoea, weight loss and gastro- intestinal polyposis. The case is reported for its rare presentation as the ectodermal changes preceded other clinical features.